PENGELOLAAN REKAM MEDIS AKTIF DI RUMAH SAKIT MATA PROVINSI NUSA TENGGARA BARAT - Dinda Rahayu, Adhitya; Subandi, Subandi (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
Active medical records are still frequently used in services, requiring fast access and proper management. The NTB Provincial Eye Hospital faces various problems such as incomplete filling of operation sheets, late file returns, and errors in file storage. This paper aims to provide an overview of the management of active medical records at the NTB Provincial Eye Hospital and to identify obstacles in its management and solutions to overcome them. The method used is qualitative with a descriptive approach. The subjects are medical record staff and the object is the management of active medical records at the NTB Provincial Eye Hospital. Data collection through interviews, observations, and documentation. The results show that the management of active medical records has been implemented through assembling, coding, indexing, file storage and retention of active to inactive files and in its management is hampered by non-compliance with file returns by inpatients, human error, and the IT department that has not been optimal in running its Hospital Management Information System (SIMRS). Therefore, the hospital needs to develop Electronic Medical Records (ER) comprehensively to overcome existing obstacles.